Sanctions for Criminal Trafficking in Persons - Febriyana Febiola Onggi (Universitas Negeri Gorontalo, 2022)
The purpose of this research is to know and analyze aboutsanctions for the perpetrators of the Crime of Trafficking in Persons at the Manado District Court. This type of research is normative research. The results of this study include prostitution, physical, sexual exploitation, utilizing one's energy and or abilities by parties who have control to gain benefits both materially and immaterially. In this case the defendant for committing the crime of trafficking in persons was found guilty, even though there was evidence that from the facts revealed in court the idea of sexual exploitation of the victim actually came from the victim herself who wanted to exploit herself. The actions of the defendant who could be blamed for allowing did not prevent the victim from doing this and the defendant complied with the victim's instructions to chat with the michat application on the victim's cellphone by showing the victim's potential customers. This means that the defendant took part in the sexual exploitation of the victim who is still a child.